Do low profile implants provide reliable stability in fixing the sternal fractures as a “fourth vertebral column” in sternovertebral injuries? - Krinner, Sebastian; Grupp, Sina; Oppel, Pascal; Langenbach, Andreas; Hennig, Friedrich F.; Schulz-Drost, Stefan (Journal of Thoracic Disease, 2017)
Background: Flexion and compression forces to the trunk can cause severe instability of the vertebral column and the anterior chest wall, mostly associated with an unstable fracture of the sternum. In combination, the worst case would be a complete disruption of the trunk. Some authors consider the sternum-rib-complex to be the fourth vertebral column. This study discusses the possibilities to treat instable trunk injuries with sternal fractures concomitant to vertebral spine fractures through anterior sternal plating employing a locked plate osteosynthesis in a low profile design instead of the use of bulky implants. Methods: 11 Patients suffering from at least one fracture of a vertebral body in combination with an unstable sternum fracture were stabilized through a locked plate osteosynthesis in low profile design at the sternum between November 2011 and October 2014. The vertebral spine injury was stabilized as well, if necessary. Patients were followed up with a look at the consolidation of the fractures and the question if any failure of the implants occurred. Results: Anterior sternal plating was uneventful in all cases. All Sternal fractures showed sufficient consolidation. No failure of implants has been seen during follow up over two years.. Conclusions: A locked plate osteosynthesis of a sternal fracture in low profile design seem to be an appropriate option for stabilization of the sternum in combined sternovertebral injuries.